Analysis of Perishable Vendor Selection to Fulfill the Need of Production Department - Pratiwi, Kadek Rani; Mataram, I Gusti Agung Bagus; Susyarini, Ni Putu Wiwiek Ary; Sadguna, I Gde Agus Jaya; Arjana, I Wayan Basi; Solihin (Jurnal Bali Membangun Bali, 2022)
Purpose: This research aims to know the main criteria in selecting perishable vendors for the production department needs at PT. Aerofood ACS, Denpasar. Design/methodology/approach: This study is a quantitative and qualitative research where its primary data col-lected through interviews, questionnaires, observations, and document studies. This study uses proportional random sampling method with the sample size of 30 respondents. Findings: The main criteria considered in the selection of perishable vendor to meet the needs of production department is quantity accuracy criteria with an average of 4.90 which was in very good intervals. Implications: The last criteria are delivery accuracy, service, quality, and the last is price.